Dynamic changes in gene expression and alternative splicing mediate the response to acute alcohol exposure in Drosophila melanogaster - Signor, Sarah (Heredity (Edinb), 2018)
Environmental changes typically cause rapid gene expression responses in the exposed organisms, including changes in the representation of gene isoforms with different functions or properties. Identifying the genes that respond to environmental change, including in genotype-specific ways, is an important step in treating the undesirable physiological effects of stress, such as exposure to toxins or ethanol. Ethanol is a unique environmental stress in that chronic exposure results in permanent physiological changes and the development of alcohol use disorders. Drosophila is a classic model for deciphering the mechanisms of the response to alcohol exposure, as it meets the criteria for the development of alcohol use disorders, and has similar physiological underpinnings with vertebrates. Because many studies on the response to ethanol have relied on a priori candidate genes, broad surveys of gene expression and splicing are required and have been investigated here. Further, we expose Drosophila to ethanol in an environment that is genetically, socially, and ecologically relevant. Both expression and splicing differences, inasmuch as they can be decomposed, contribute to the response to ethanol in Drosophila melanogaster. However, we find that while D. melanogaster responds to ethanol, there is very little genetic variation in how it responds to ethanol. In addition, the response to alcohol over time is dynamic, suggesting that incorporating time into studies on the response to the environment is important.